Science Laboratory Management: State Owned JuniorHigh School Semesta Semarang - Jatmiko, Ilham Subur (2012)
The objectives of the are three objectives of this study (1) this study are to describe setting of Science laboratory room; (2) this study are to describe characteristic of Science laboratory material management; (3) this study are to describe the satisfaction of using the Science laboratory. It is a qualitative research using ethnography design. The informants are the principal, teacher, and student. Technique of data collection uses observation, interview, and documentation. Method of data analysis uses data collection, data reducation, data display, and conclusion. Data validity of this research includes credibility, transferability, dependability, and conformability. The results of this study there three subjects are (1) Designing of Science laboratory room at Junior High School Semesta Semarang has been relevant to the standard of laboratory management. Science laboratory has several rooms such as a room to store practicum tools which is located in the back of the room. The tool storage room measuring 3 m x 10 m, with a door to enter and exit the room. The arrangement of tables and chairs in the Science laboratory is tailored with the need of teaching and learning process. There are a white board and LCD in front of the laboratory room. There are 24 windows and four sinks in the Science laboratory of Junior High School Semesta Semarang. There are no fire-extinguisher and P3K box in the Science laboratory of Junior High School Semesta Semarang. (2) The management of Science laboratory at Junior High School Semesta Semarang is done based on the educational system applied that is moving class where students stay on their classroom based on the subject to be followed. The reference books at are collected from Indonesian and Turkey. The reference books are stored in cabinet located in the back of the Science laboratory room. (3) The satisfaction of using Science laboratory is influenced by the completeness of available facilities and infrastructure in a laboratory room. The facilities and infrastructure include practicum room, and storage room of practicum tools. Tools in the laboratory are stored in the glass display cabinet in order to facilitate teachers to control it. The chairs and tables can be moved when conducts a discussion for the material being taught. The available of ventilation in a room is urgently needed to help the air circulation in the room. The sink in the laboratory is very helpful for students when the practice is finished.